Caries-preventing effect of a hydroxyapatite-toothpaste in adults: a 18-month double-blinded randomized clinical trial - Elzbieta Paszynska; Malgorzata Pawinska; Joachim Enax; Frederic Meyer; Erik Schulze zur Wiesche; Theodor W. May; Bennett T. Amaechi; Hardy Limeback; Amadeusz Hernik; Justyna Otulakowska-Skrzynska; Anna Krahel; Inga Kaminska; et al. (Frontiers Media S.A., 2023)
BackgroundDental caries is a worldwide challenge for public health. The aim of this 18-month double-blinded, randomized, clinical trial was to compare the caries-preventing effect of a fluoride-free, hydroxyapatite toothpaste (test) and a toothpaste with sodium fluoride (1450 ppm fluoride; positive control) in adults.MethodsThe primary endpoint was the percentage of subjects showing no increase in overall Decayed Missing Filled Surfaces (DMFS) index. The study was designed as non-inferiority trial. Non-inferiority was claimed if the upper limit of the exact one-sided 95% confidence interval for the difference of the primary endpoint DMFS between test and control toothpaste was less than the predefined margin of non-inferiority (Δ ≤ 20%).ResultsIn total, 189 adults were included in the intention-to-treat (ITT) analysis; 171 subjects finished the study per protocol (PP). According to the PP analysis, no increase in DMFS index was observed in 89.3% of subjects of the hydroxyapatite group and 87.4% of the subjects of the fluoride group. The hydroxyapatite toothpaste was not statistically inferior to a fluoride toothpaste with regard to the primary endpoint.ConclusionHydroxyapatite was proven to be a safe and efficient anticaries agent in oral care.Clinical trial registrationNCT04756557.